PRUNING Araucaria angustifolia FOR KNOT-FREE TIMBER PRODUCTION - Dobner Jr., Mário (Floresta, 2022)
Although A. angustifolia is currently economically unimportant, the worldwide trend of conservation through the sustainable use of natural resources together with an intense discussion of governmental regulations and the recent results of genetic breeding started in the 1970s are delivering promising perspectives for a new wave of plantations. This study aimed to determine optimal pruning strategies by evaluating the diameter and height growth of young A. angustifolia trees as affected by different pruning intensities. Pruning quality in terms of occlusion and defect-core size were also investigated. At the age of 6 years, the pruning experiment was started by conducting six different pruning intensities, named after the number of whorls left after pruning (0, 2, 4, 6, and 8), as well as unpruned (U) trees as a control. From the results obtained in the present study, it was concluded that pruning intensity had a significant negative effect on the growth of young A. angustifolia trees. Diameter was more affected than height growth. Pruning young A. angustifolia trees for knotty-free timber production must be conducted keeping 8 whorls after the intervention if no negative effect in current annual increment in diameter is to be observed when compared to unpruned trees. A defect core of 15 cm seems to be a feasible target for the species regarding optimal pruning intensity to avoid losses in diameter growth. This is strongly dependent on a fast occlusion process, which, in turn, is a result of a careful pruning technique.